Ethic Policy Forum: Inclusion of Latin American Ethnic Minorities in Clinical Trials - Muñoz del Carpio Toia, Agueda (2022)
Objetive: To analyze the normative and ethical aspects related to the inclusion of ethnic minorities in clinical trials in Latin America and the Caribbean. Methods: The results of the ethical and normative analysis carried out by the group of researchers in bioethics of the Ethic Policy Forum are presented; forum for analysis, discussion and formulation of proposals in policies and regulations related to aspects of ethics in research in the countries of Latin America and the Caribbean, constituted by the Institute for the Evaluation of Technologies in Health and Research of the Social Security of Health of Peru, the Universidad Católica Santa María de Arequipa, Peru and the International Network of Collective Health and Intercultural Health of the Autonomous University of the State of Mexico. Results: It is evident that ethnic minorities are not adequately represented in clinical trials in Latin America and the Caribbean and the regulations in this regard are not standardized, or do not exist in all the countries of the Region. Trials with ethnic minorities can have benefits but also potential risks and ethical conflicts, which require an adequate assessment of vulnerabilities, effective support in informed consent and the research process, by Research Ethics Committees trained in intercultural health and research ethics. research with indigenous peoples and Afro-descendants. Conclusion: Clinical trials should include ethnic minorities, with potential benefit from research products. Research must be developed under ethical and regulatory principles that protect these minorities.